Cutting performance of multilayer coated tungsten carbide in milling of wood composites. (3rd April 2019) - Pangestu, Kidung Tirtayasa Putra; Darmawan, Wayan; Nandika, Dodi; Usuki, Hiroshi
ABSTRACT: The application of surface coating technology to tungsten carbide tools has been carried out to adapt the development of advanced wood composite technology. The purpose of this research was to investigate the cutting performance (wear resistance, surface roughness, and noise level) of TiAlN, TiAlN/TiSiN, and TiAlN/TiBON coated tungsten carbide in cutting wood composites. The wood composites of asbestos, wood plastic composite (WPC), laminated veneer lumber, and strand board were cut by the coated carbide tools in a computer numerical control router. The results show that the differences in structure among the wood composites resulted in the difference in clearance wear and surface roughness phenomenon. The abrasive materials in WPC and asbestos generated high clearance wear on the coated carbide tools tested. TiAlN/TiBON coated carbide tool provided the highest wear resistance, the lowest noise level, and better surface roughness.